Estimation of the wet bulb globe temperature from temperature and relative humidity gradients - Pinto Junior, Osvaldo Borges; Silveira, Sérgio Wagner Gripp; De Musis, Carlo Ralph; Annunciação, Luiz de; Pereira, Osvaldo Alves (Ciência e Natura, 2018)
In this study, maps of the estimated heat index for a preservation area in the city of Cuiabá, Mato Grosso, Brazil, were constructed using temperature and relative humidity gradients. Understanding microclimate variable behavior is useful for explaining the relationship between urban sprawl and increased environmental distress. The implementation and preservation of green areas is one way to mitigate the environmental impacts of human activities. Urban parks are one common type of green area in cities. According to ISO 7243, heat exposure can be assessed using the Wet Bulb Globe Temperature (WBGT). This study used multivariate statistical techniques and ordinary kriging to produce a WBGT map of the park during the dry and rainy seasons. Places with heat or freshness islands were identified. Locations along hiking trails and areas with exercise equipment were analyzed for WBGT tendencies in order to propose precautionary heat exposure measures.